The epidemiology of pediatric bone and joint infections in Cambodia, 2007-11. - Stoesser, N; Pocock, J; Moore, C; Soeng, S; Hor, P; Sar, P; Limmathurotsakul, D; Day, N; Kumar, V; Khan, S; Sar, V; Parry, C (Oxford University Press, 2013)
There are limited data on osteoarticular infections from resource-limited settings in Asia. A retrospective study of patients presenting to the Angkor Hospital for Children, Cambodia, January 2007-July 2011, identified 81 cases (28% monoarticular septic arthritis, 51% single-limb osteomyelitis and 15% multisite infections). The incidence was 13.8/100 000 hospital attendances. The median age was 7.3 years, with a male/female ratio of 1.9:1; 35% presented within 5 days of symptom onset (median 7 days). Staphylococcus aureus was cultured in 29 (36%) cases (52% of culture-positive cases); one isolate was methicillin-resistant (MRSA). Median duration of antimicrobial treatment was 29 days (interquartile range 21-43); rates of surgical intervention were 96%, and 46% of children had sequelae, with one fatality. In this setting osteoarticular infections are relatively common with high rates of surgical intervention and sequelae. Staphylococcus aureus is the commonest culturable cause, but methicillin-resistant S. aureus is not a major problem, unlike in other Asian centers.